2018
DOI: 10.1097/qai.0000000000001598
|View full text |Cite
|
Sign up to set email alerts
|

Medication Adherence in a Nationwide Cohort of Veterans Initiating Pre-exposure Prophylaxis (PrEP) to Prevent HIV Infection

Abstract: First-year adherence with TDF/FTC was overall high in a nationwide cohort of PrEP users. Differences in adherence by age, race, and sex suggest potential for disparities in PrEP effectiveness in routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 11 publications
4
35
0
Order By: Relevance
“…We found that PrEP discontinuations were more likely to occur among persons who were younger, who identified as transgender women, and who had multiple mental health disorders. Our findings corroborates prior studies that have found an association between younger age and challenges accessing or continuing with PrEP [14,30,31] and highlights additional sub-populations, including transgender women and those with mental health disorders, for whom intensive and/or tailored support for continued PrEP use may be beneficial. Because HIV incidence rates among young MSM and transgender women are among the highest in any sub-population nationally [32], and because mental health diagnoses have been associated with HIV risk behaviours [33,34], addressing ineffective PrEP use in these groups should be prioritized.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We found that PrEP discontinuations were more likely to occur among persons who were younger, who identified as transgender women, and who had multiple mental health disorders. Our findings corroborates prior studies that have found an association between younger age and challenges accessing or continuing with PrEP [14,30,31] and highlights additional sub-populations, including transgender women and those with mental health disorders, for whom intensive and/or tailored support for continued PrEP use may be beneficial. Because HIV incidence rates among young MSM and transgender women are among the highest in any sub-population nationally [32], and because mental health diagnoses have been associated with HIV risk behaviours [33,34], addressing ineffective PrEP use in these groups should be prioritized.…”
Section: Discussionsupporting
confidence: 90%
“…A retrospective chart review at an academic health system in New York found that retention in PrEP care after six months was 42%. [17] In a national study of over 1000 PrEP users at the Veterans Health Administration, 44% of PrEP users discontinued PrEP within the first year [14], and 38% of PrEP users at a community-based clinic in San Francisco discontinued PrEP by 13 months [13]. Similarly, 26% of nearly 5000 patients who initiated PrEP between 2012 and 2017 at an integrated healthcare organization in Northern California discontinued PrEP [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Finally, PrEP discontinuation is common, with one study finding that 44% of initiators discontinued within one year. 25,26 Prescription renewals or repeat pharmacy fills could be used to derive measures of duration of use, such as the mean percentage of days covered by PrEP in a given time period, 25-28 but this aspect of the data has yet to be described.…”
Section: Numerators For Prep Coverage: Measures Of Prep Use and Accessmentioning
confidence: 99%
“…However, few studies have explored the influence of alcohol and drug use specifically in the context of PrEP care. Two studies using medication refill data from large healthcare systems showed that patients with substance use diagnoses had fewer days covered by PrEP [32][33] . However, neither alcohol nor other substance use were associated with PrEP drug levels over time in the iPrEx OLE or DEMO Project 10,11 .…”
Section: Introductionmentioning
confidence: 99%